Pengembangan Media Pembelajaran Matematika dengan Bantuan Canva pada Materi Peluang - Fauzia, Nur (Journal of Mathematics Learning Innovation, 2024)
The aim of this research is to describe the process and find out the results of the development of Canva-assisted mathematics learning media for class VIII opportunity material at SMP Negeri 4 Enrekang and to find out whether the media can help students understand opportunity material. This type of research is research and development using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model developed by Robert Maribe Branch. This product trial was carried out on 28 students in class VIII B at SMP Negeri 4 Enrekang. The ADDIE model in Analysis, researchers analyzed the curriculum, materials, needs and characteristics of students. Then in Design, the template design and animation are carried out. Meanwhile, in Development, media creation, media revision and media assessment are carried out. These results show that the level of validity based on expert validation is at the "very valid" criterion. In the practicality response the criteria were "very practical" and the level of implementation of media use was in the "very good" category. Meanwhile, the level of media effectiveness based on test scores on student learning outcomes is categorized as "medium", the level of student activity is in the "very good" category and student responses are in the "very positive" category. Based on the results of the data analysis carried out, it can be concluded that mathematics learning media Canva's assistance in opportunity material for class VIII SMP Negeri 4 Enrekang was declared quality and met the criteria of being valid, practical and effective